Oral Clinical Findings in Cadaver with Tuberculosis: A Case Report - Azizah, Anna; Wahyu, Nadilla I.; Rahmadhani, Ayu; Soedarsono, Nurtami; Yuniastuti, Mindya; Suhartono, Antonius W.; Syarifudin, Mohammad A.; Fonataba, Anthon G. (e-GiGi, 2025)
Abstract: Tuberculosis (TB) is a long-lasting infectious disease that usually affects the lungs (pulmonary TB), but can also affect other organs and systems (extra-pulmonary TB). Oral TB is uncommon, particularly primary oral tuberculosis which predominantly affects young adults, and the tongue is the site most frequently affected. This case report aimed to discuss the manifestation of TB in the hard palate, focusing on observation from a cadaver and providing a thorough analysis of the oral clinical symptoms. We reported a case of unidentified 42-year-old female body that  was found dead and brought to Dr. Cipto Mangunkusumo Hospital for an autopsy. Poor oral hygiene was found. In the palate, there was bone defect on palatum durum regio teeth 21 22 near to the incisive foramen. Pink teeth was discovered in the anterior part of the lower jaw. Based on the autopsy report, the cause of death was tuberculosis. In conclusion, although tuberculosis of the palate is infrequent, it should be included as a potential cause of palatal perforation during diagnostic evaluations. Additionally, it is crucial to conduct a comprehensive investigation into the primary site of tuberculosis in cases involving palatal tuberculosis. Keywords: oral tuberculosis; palatal perforation; pink teeth phenomenon